2022
DOI: 10.1142/s0219455422501218
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Form Demonstration and Shake Table Verification of Damping Effect on the Seismic Energy

Abstract: This paper discusses closed-form demonstrations of the damping effect for a basic mass, spring, and damper (MSD) and a single degree of freedom (SDOF) system that are exposed to harmonic loading. Initially, the energy balance equations of the systems were solved in closed form by considering the damping ratio and loading frequency. Verification of the solutions obtained for SDOF systems is achieved by shake table tests. Based on the analytical and experimental results, it was found that the damping effect is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this context, a comparison was conducted between the responses of structures under dynamic and static loadings by solving both the equation of motion and the energy equilibrium equation. The dynamic amplification factors (dynamic response/static response) derived from the solutions of the equation of motion 48 and the energy equilibrium equation 49 for an SDoF system are presented in Figure 17. These figures illustrate that loading with very low and very high frequency ratios to the natural frequency leads to lower responses compared to those calculated by static procedures.…”
Section: Evaluation Of the Proposed Record Selection And Scaling Meth...mentioning
confidence: 99%
“…In this context, a comparison was conducted between the responses of structures under dynamic and static loadings by solving both the equation of motion and the energy equilibrium equation. The dynamic amplification factors (dynamic response/static response) derived from the solutions of the equation of motion 48 and the energy equilibrium equation 49 for an SDoF system are presented in Figure 17. These figures illustrate that loading with very low and very high frequency ratios to the natural frequency leads to lower responses compared to those calculated by static procedures.…”
Section: Evaluation Of the Proposed Record Selection And Scaling Meth...mentioning
confidence: 99%
“…Lin et al (2013) showed that an efficient and sufficient IM should consider both earthquake and structural characteristics. Further, Sandıkkaya and Akkar (2017) mentioned that ground motions can be characterized based on amplitude, duration, and frequency content which is also related to the imparted seismic energy, (Akiyama (1985); Güllü et al (2022b); Güllü et al (2023)).…”
Section: Introductionmentioning
confidence: 99%